Meningkatkan Potensi Toga Menjadi Jamu Serbuk Instan Berbasis Industri Rumahan Mbak Rika Di Dukuh Wonorejo, Bedrug, Pulung - Sri Kantun; Muhammad Misbahudin (Social Science Academic, 2025)
In In Dukuh Wonorejo there is a home industry that processes family medicinal plants into instant powders for consumption labeled “various essences of toga mbok jem” which is one of the medicinal plant businesses in Bedrug village, here you can see how great the opportunities there are in the village If Bedrug is developed and can be recognized by many people through the processing of family medicinal plants into instant herbal powder, various kinds of processed products that can be consumed practically by presenting brewed ready-to-eat consumption. The steps taken in this activity are using the ABCD approach method, interviews and direct observation with the owner of a variety of toga saris, namely Ms. Rika. The purpose of this activity is to introduce and educate the general public about consuming instant powdered herbal medicine. From the activities carried out, it can be seen that various processed products are in demand by customers from all walks of life, from young people to adults. Marketing of home industry products through social media/online and offline. The conclusion that can be drawn from this activity is that the processing of family medicinal plants into instant powdered herbal medicine can increase the interest of the public who are fans of more practical herbal medicine. From processing family medicinal plants to instant herbal powder, new business ideas can be created. With observation and interview activities, we hope to add knowledge, insight, and knowledge as well as innovation for people who have abundant family medicinal plants so they can process them to create business opportunities that have high selling value.